Diabetes mellitus and HIV as co-morbidities in tuberculosis patients of rural south India - Soham Gupta; Vishnu Prasad Shenoy; Indira Bairy; Hiresave Srinivasa; Chiranjay Mukhopadhyay (Elsevier, 2011)
Summary: Objectives: Incidence of tuberculosis (TB) is greatest among patients with impaired immunity. India is experiencing a double epidemic of HIV and diabetes mellitus (DM), both of which are strongly associated with immuno-suppression. This study aimed to discover the prevalence of HIV and DM in both the pulmonary and extra-pulmonary TB patients of rural south India, retrospectively. Methods: Medical records of 192 microbiologically diagnosed pulmonary TB and 37 extra-pulmonary TB patients were thoroughly studied and data were extracted. The frequency distribution of HIV and DM was evaluated along with other demographic details such as age, sex and occupation in both groups. Results: The mean age of the pulmonary TB patients was 41.11 ± 15.7 years, with significantly higher (p < 0.0001) preponderance of DM (31.8%) over HIV (8.9%). 72.13% of the diabetic patients belonged to the age group of 41-60 years. Extra-pulmonary TB patients had a mean age of 34.62 ± 12.9, years with a significantly higher (p < 0.006) HIV prevalence of 32.43% over DM (5.4%). 75% of the HIV patients belonged to the age group of 41-60 years. Occupationally, the majority of the pulmonary TB patients were agricultural labourers (25.2%) while the majority of the extra-pulmonary TB patients were housewives or self employed (18.92%). Conclusion: Though more importance is being given to HIV-TB coinfection, we cannot overlook DM, which showed a significantly higher prevalence in pulmonary TB patients compared to HIV. The rising prevalence of DM in high TB burden countries may adversely affect TB control. Keywords: Tuberculosis, HIV, Diabetes mellitus, Occupation